Optical gaps of free and embedded si nanoclusters: density functional theory calculations - Hadjisavvas, George C.; Idrobo, Juan Carlos; Kelires, Pantelis C. (My University, 2010)
The optical gaps of free and embedded Si nanoclusters are studied within the time-dependent local-density approximation. The effects of deformation, the bonding of individual O atoms on the surface, and coverage by SiO 2 layers on the highest occupied molecular orbital-lowest unoccupied molecular orbital and optical gaps are systematically compared. It is found that all three can have a significant impact. Oxygen bonded to the surface and deformation cause the greatest reduction in the gaps, particularly in combination.
Keywords: Porous silicon; Photoluminescence; Silicon nanocrystals